SURFACE MORPHOLOGY OF SPUTTERED TITANIUM-ALUMINUM-NITRIDE COATINGS - Esmar Budi; M. Mohd. Razali; A.R. Md. Nizam (Spektra: Jurnal Fisika dan Aplikasinya)
A study on the surface morphology of sputtered TiAlN coatings is presented. The coatings were deposited by DC magnetron sputtering on tungsten carbide insert tools. The surface morphology was characterized by using Atomic Force Microscopy (AFM), and the surface roughness was indicated by RMS roughness value. It was observed that the TiAlN coating surface morphology was rough as the negative substrate bias and nitrogen flow rate are increased. The evolution of the sputtered TiAlN coatings surface morphology was due to the competition between particle diffusion and re-scattering effect during the sputtering process. At high negative substrate bias and nitrogen flow rate, the re-scattering effect was prominent, leading to the high roughness of the sputtered TiAlN coating surface.